Budaya dan Iklim Organisasi Dalam Meningkatkan Kedisiplinan Siswa - Azizah Pratiwi; Siti Nurul Salma; Ermita; Fifin Wildanah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The purpose of this paper is to find out how organizational culture and climate affect student discipline in schools or educational institutions. This study uses a literature study method. Disciplined character must be instilled when children are at school. If the school has a good social environment and maintains the value of discipline, students will also develop into disciplined and responsible personalities. To foster this discipline value, all school residents must also apply the value of discipline in themselves, starting from the principal, teachers, staff and other educational professionals. A conducive and calm organizational climate and climate will affect the attitude of discipline in students. The culture or climate in schools will affect the process and also the results of student education at school. In the school environment, teachers play an important role in creating conditions that foster character values. Teacher behavior influences students' personalities by creating an environment in schools with values such as character building, independence and integrity.